2013
DOI: 10.1016/j.drugalcdep.2012.06.019
|View full text |Cite
|
Sign up to set email alerts
|

On the predictive validity of automatically activated approach/avoidance tendencies in abstaining alcohol-dependent patients

Abstract: Background. Prominent addiction models posit that automatically activated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
77
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 48 publications
11
77
4
Order By: Relevance
“…This finding is quite surprising because the self-reported level of alcohol avoidance has been found to correlate negatively with automatic approach tendencies (Barkby et al, 2012). However, recent findings report that alcohol-dependent patients inclined to avoid alcohol show higher relapse rates, suggesting that alcohol avoidance could hide approach drives (Spruyt et al, 2013). The second factor that could explain the absence of inhibition deficit towards alcohol-related cues in heavy drinkers is the low impulsivity level found in our participants.…”
Section: Discussioncontrasting
confidence: 46%
“…This finding is quite surprising because the self-reported level of alcohol avoidance has been found to correlate negatively with automatic approach tendencies (Barkby et al, 2012). However, recent findings report that alcohol-dependent patients inclined to avoid alcohol show higher relapse rates, suggesting that alcohol avoidance could hide approach drives (Spruyt et al, 2013). The second factor that could explain the absence of inhibition deficit towards alcohol-related cues in heavy drinkers is the low impulsivity level found in our participants.…”
Section: Discussioncontrasting
confidence: 46%
“…Substance-related stimuli have been shown to automatically (a) grab the user's attention (e.g., Field and Cox 2008), (b) activate approach/avoidance tendencies (e.g., Eberl et al 2013;Spruyt et al 2013;Wiers et al 2011), and (c) activate implicit attitudes from memory (e.g., Houben et al 2010c;Wiers et al 2002). Nevertheless, only a limited number of studies have documented the extent to which these automatic processes drive relapse in abstaining patients.…”
Section: Discussionmentioning
confidence: 99%
“…Two-process models of addiction therefore predict that the impulsive system will exert primary control over behavior under conditions of reduced motivation and/or opportunity to engage in reflective processing (see also Fazio and Towles-Schwen 1999). Crucially, the capacity to engage in reflective processing is assumed to vary as a function stable differences between individuals (e.g., Farris et al 2010;Lindgren et al 2014;Thush et al 2008;Spruyt et al 2013; but see Pieters et al 2012) as well as temporary factors such as cognitive load, fatigue, and stress (Wiers et al 2010). Accordingly, two-process models of addiction can readily explain the observations that (a) it is difficult to abstain from substance abuse and (b) relapse rates in abstaining patients are typically very high.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These tasks reveal that in heavy drinkers who are not seeking treatment, alcohol cues evoke automatic approach tendencies (Field et al, , 2011Wiers et al, 2009;Christiansen et al, 2012;Sharbanee et al, 2013a,b;, and in some studies the strength of these approach tendencies was associated with the strength of subjective craving . A different pattern is seen in alcohol-dependent patients: one study reported no reliable tendency to approach or avoidance (Barkby et al, 2012) whereas another study found an automatic avoidance tendency, the strength of which was predictive of subsequent relapse (Spruyt et al, 2013). One explanation for these findings is that the standard version of the SRC task yields an index of automatic approach that is relative to avoidance.…”
Section: Introductionmentioning
confidence: 98%